ANALISIS PERBANDINGAN KUNGFU WING CHUN DARI TIONGKOK DAN PENCAK SILAT MERPATI PUTIH DARI INDONESIA - Wandayani Goeyardi (Puitika)
Martial art is one of physical exercises. Martial arts nowadays are gaining in popularity. In addition to sports, martial arts are learned to protect ourselves from various kinds of attacks. As the time progressed, martial arts increasingly popular all over the world, including China and Indonesia. China has various types of martial arts like kungfu. Kungfu is subdivided into several types, one of them is wing chun. In Indonesia, there are also various types of martial arts. Pencak silat that scattered throughout the country is Merpatih Putih. Unlike China, this type of martial arts such as Merpati Putih is also a subdivision of martial arts. Not only the reference and classification that are different, Chinese and Indonesian martial arts also have other values such as moves. Based on this problem, the comparisons found in kungfu wing chun and Pencak Silat Merpati Putih will be examined. Movement and function in this research refers to wing chun college in Malang city named Logical Wing Chun and Merpati Putih Indonesia.